Получение материала на основе bSiC и углеродных волокон электродуговым методом; Материаловедение; № 10 - Пак А. Я. Александр Яковлевич; Ивашутенко А. С. Александр Сергеевич; Болотникова О. А. Ольга Александровна; Захарова А. А. Алена Александровна (2018, 2018)
Заглавие с экрана